Physicochemical and biological properties of a new bioceramic root canal filling material for primary teeth - Ochoa Rodríguez, Victor Manuel [UNESP] (2022)
An ideal root canal filling for primary teeth should not hinder the eruption of permanent successor teeth, but rather, should be resorbed as the primary teeth roots are physiologically resorbed. Bio-C Pulpecto - Bio CP (Angelus, Londrina, Brazil) was recently developed as the first bioceramic filling material for primary teeth. The objectives of publication 1 were to evaluate radiopacity, setting time, pH, cytocompatibility and the potential for mineralization of Bio-CP compared to Calen thickened with zinc oxide (Calen-ZO) and zinc oxide eugenol (ZOE). The physicochemical properties were evaluated according to ISO 6876. Saos-2 (human osteoblast-like lineage) exposed to material extracts were subjected to methylthiazolyl tetrazolium, neutral red, alkaline phosphatase (ALP) activity and production of mineralized nodule. The results were analyzed using one-way or two-way ANOVA and Tukey or Bonferroni post-tests (α=0.05). All materials showed radiopacity greater than 3 mm Al. Bio-CP had a lower pH than Calen-ZO, but higher than ZOE. Calen-ZO and Bio-CP did not set. The ZOE setting time was 110 min. The order of cytocompatibility was Calen-ZO > Bio-CP > ZOE (1:2, 1:4 dilutions) and Calen-ZO > Bio-CP = ZOE (1:12, 1:24 dilutions) and Calen-ZO = Bio - CP>ZOE (dilution 1:32). Bio-CP induced greater ALP activity at 7 days, and greater production of Cal-mineralized proteins, compared to greater numbers of people (p<0.05). The objectives of publication 2 were evaluated for solubility (mass loss), using modified methodology from ISO 6876; filling capacity, volumetric change and presence of voids, by means of micro computed tomography (micro-CT), of Bio-CP in comparison with Calen-ZO and ZOE. In addition, the distribution of elements on the surface of the materials and the crystalline phases of Calen-ZO and Bio-CP were evaluated by energy scattering X-ray scanning electron microscopy (SEM-EDX) and X-ray diffraction (XRD). The materials were placed in polyethylene tubes of 1 or 2 mm in diameter and immersed in water or PBS (Phosphate-Buffered Saline) for 30 days. Data were analyzed by two-way ANOVA and Tukey or Kruskal-Wallis and Dunn (α=0.05). Solubility was greater than 7% for all materials; the order was ZOE>Calen-ZO=Bio-CP. Calen-ZO and Bio-CP were more soluble in water than in PBS. Most materials showed higher solubility in 2 mm tubes, both in PBS and in water. Only Calen-ZO and ZOE were analyzed on micro-CT because Bio-CP separated into two phases during scanning. There was no difference in filling capacity between the materials. Calen-ZO had greater volumetric loss and presence of voids than ZOE in water, but there was no difference in PBS. Precipitates on the surface of BioCP and Calen-ZO, corresponding to hydroxyapatite, were drawn after printing in PBS. It was concluded that BioCP presented adequate physicochemical properties, citocompatibility and potential to induce mineralization. All materials showed adequate filling capacity. Bio-CP and Calen-ZO showed lower solubility than ZOE, regardless of immersion medium and tube diameter, except for the 2 mm tube immersed in PBS, and produced hydroxyapatite when immersed in PBS. Micro-CT was not suitable for Bio-CP evaluation. Although Bio-CP has the potential to become a suitable material for filling primary teeth, its composition needs to be revised to achieve chemical stability.